2009
DOI: 10.1111/j.1439-0272.2009.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Can a cumulus cell complex be used to select spermatozoa for assisted reproduction?

Abstract: Since the onset of intracytoplasmic sperm injection, researchers have intensified the search for the ideal spermatozoa to be used for injection. The aim of this study was to record the functional role of cumulus cell interaction with human spermatozoa as far as capacitation, acrosome reaction, morphology, zona binding and chromatin packaging quality are concerned. Using a previously described cumulus oophorus model, we recorded specific sperm functional aspects of sperm populations that transverse a cumulus ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
5
17
0
1
Order By: Relevance
“…A capillary-cumulus model was established to study the role of the cumulus in the selection of sperm for fertilization and penetrating sperm had a higher morphology, capacitation, acrosome reaction, progressive motility, linearity, ZP binding ability (70), and protamination (71). This data was confirmed in a later study and it was suggested that the capillary-cumulus model could be used to select sperm for ICSI (72).…”
Section: Cumulus Penetrationsupporting
confidence: 63%
“…A capillary-cumulus model was established to study the role of the cumulus in the selection of sperm for fertilization and penetrating sperm had a higher morphology, capacitation, acrosome reaction, progressive motility, linearity, ZP binding ability (70), and protamination (71). This data was confirmed in a later study and it was suggested that the capillary-cumulus model could be used to select sperm for ICSI (72).…”
Section: Cumulus Penetrationsupporting
confidence: 63%
“…Although our work has focused on sperm DNA damage it is quite possible that other yet poorly understood biological properties of sperm may be as critical in selecting optimal sperm. Existing means of evaluating sperm in a non-consumptive manner include the utilization of cumulus cells and zonae pellucida of immature oocytes to improve selection of optimal sperm [Black et al 2010;Franken and Bastiaan 2009;Paes Almeida Ferreira de Braga et al 2009]. Other studies have considered the use of Raman microspectrometry; however, the technique has not been thoroughly evaluated in assessing if it improves IVF outcomes [Huser et al 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Among the cheaper methods is the utilization of cumulus cells in a Pasteur pipette 165 or zonae pellucidae of immature oocytes [162][163][164] as there are no differences in normal sperm morphology and DNA integrity of zona-bound sperm between mature and immature oocytes. 89 Franken and Bastiaan 165 showed that the percentages of cells with normal morphology, good quality chromatin condensation and tightly zona-bound spermatozoa were significantly higher in the cumulus-penetrated fraction of spermatozoa and speculate that this might be a possible means for the selection of functional spermatozoa for ART. However, for both approaches, the availability of cumuli and zonae pellucidae might be a problem, which would limit the applicability of the methods.…”
Section: Future Development Of Sperm Preparation Techniquesmentioning
confidence: 99%